Why firms lose their ISO 9001 certification: evidence from Portugal - Candido, Carlos (2020)
More than one million certified companies must choose, every three years, whether to renew or to withdraw from ISO 9001 certification. This paper investigates whether ISO 9001 decertification decision is driven by economic motivations. Using standard event-study methods, the paper looks into this question by comparing the abnormal performance of a sample of Portuguese firms that lose their certification with that of similar, non-event, firms. The paper finds no statistically significant differences in the economic performance of these two sets of firms in their post-ISO certification period. Such evidence suggests that economic underperformance is not the reason why companies are ISO decertifying and further suggests that the decision to decertify is economically irrelevant. The study advances possible explanations for this (ir)relevancy and puts forwards implications for theory and for the ISO 9001 governance system. The governance system must change in order to increase the economic benefits that organisations can expect to gain from ISO (re)certification. This is the first study assessing the impact of ISO 9001 certification on firms that subsequently lost the certificate.